Physical properties of magnesian lime mortars - PAVIA, SARA (My University, 2010)
Magnesian lime is made from dolomitic limestone. The properties of magnesian lime mortars are not yet clearly established: some authors claim that Mg-lime has no hydraulicity and produces poor quality mortars that fracture, while others state that it produces quality hydraulic mortars. Here, Mg-lime was produced by burning magnesium limestone in a traditional limekiln. Mortars were made with increasing proportions of Mg-lime and calcium lime (CL90), and tested according to both European and ASTM Standards, and RILEM recommendations. Shrinkage, compressive and flexural strengths, absorption, capillary suction, density and porosity were evaluated, and the relationships between workability (measured as initial flow), water demand and strength investigated. The process of lime production evidenced that fabrication parameters are instrumental on the quality of Mg-lime and the subsequent mortar?s performance. Temperatures over 900?C induced over-burning resulting in clinker formation and a lack of reactivity. The choice of kiln fuel and burning arrangement proved essential in order to reach a homogeneous calcination; and sieving of unslaked and over/underburnt particles as well as trials to determine raw feed proportions, were needed in order to avoid poor quality lime. Testing evidenced that the higher the Mg content, the greatest the mortar?s shrinkage. However, shrinkage did not reach unacceptable values and cracking didn?t occur. It was also evidenced that the Mg-lime possessed a lower water demand than the CL; and that Mg mortars behave well towards fluids (their capillary suction was lower and their porosity and absorption similar to those of CL90 mortars). The results also suggest that Mg-lime mortars possess compressive and flexural strengths equivalent to those of some feebly-hydraulic lime mortars: Mg-lime strength falls within the EN459-1 strength requirements for natural feebly-hydraulic lime. This research concludes that, providing production is correct, Mg-limes produce reliable masonry mortars which will shrink further but will possess a lower water demand and a slightly higher mechanical strength than CL mortars.
PUBLISHED
Keywords: Mg-lime, CL90, shrinkage, compressive and flexural strength, absorption, suction, density, porosity, workability, water demand.